Impact of COVID-19 infections and vaccination on menstrual cycle symptoms in the south of Jordan: a cross-sectional study - Mohammad A. Abu-Lubad; Munir A. Abu-Helalah; Mohammad S. QawaQzeh; Esra'a F. Alahmad; Malak M. Al-Tamimi; Mohammad K. Ruba'I; Sahm H. Etoom; Rawan K. Alfayoumi; Fatima E. Aldaoudeyeh; Ekram A. AlAbabneh; Ahlam M. Al-kharabsheh; Hussam Alshraideh (SpringerOpen, 2024)
Abstract Background Several recent studies have highlighted the need for more evaluation of the impact of COVID-19 infections and vaccines on the reproductive system and menstruation. This study aimed to assess the impact of COVID-19 infection and vaccines on menstrual symptoms. Methods A cross-sectional survey utilizing face-to-face interviews from January 1 to 31 March 2022 was conducted in the city of Al-Karak in southern Jordan. The questionnaire included sociodemographic characteristics, medical and reproductive history, the contraceptive method used if any, menstrual cycle (MC) status, previous medical and drug history, and the impact of infection and vaccination on the MC. Results The study questionnaire was completed by 400 participants with a mean age of 32.1±12.6 years. Regarding the history of COVID-19 infections, 33.8% of the participants reported a history of confirmed COVID-19 infections, 77.8% of them did not report any menstrual changes following the infection, while the remaining 22.2% reported changes in menstruation. The most commonly reported post-COVID-19 manifestations were irregular (27.6%) and light menstrual cycle (MC) (24.15) or dysmenorrhea (24.1%). Heavy menstruation was reported by 17.2% of participants post-COVID-19 infection. Two-thirds of the study participants (66.6%) reported no changes in the MC following the administration of the COVID-19 vaccine. The most reported symptoms for those who experienced changes in the MC following the vaccination were irregular cycle (13.1%), heavy menstruation (7%), and light menstruation (7%). Other reported symptoms were dysmenorrhea (4.6%), intermenstrual bleeding (1.2%), and amenorrhea (0.5%). Conclusion This study revealed minor changes in the MC following COVID-19 infections and administration of the COVID-19 vaccine. These findings are consistent with published reports. It is recommended that future clinical trials for new vaccines for women of childbearing age include outcomes related to sex hormones and MC. Women should be encouraged to take the vaccines and report symptoms to healthcare professionals for further assessment.